Hannah Montana on tour : cia from Rome - PERELMAN, HELEN; HELEN PERELMAN (New York Disney Press, 2009)
Miley Stewart takes her world tour to Rome.
Keywords: Miley Stewart traveling internationally for her worldwide concert tour; Miley Stewart navigating the pressures of her first international concert while attempting to enjoy the experience of being in a new country